State mechanisms of collecting ecological payments in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
Article discussed the ways and rules of law, оne of the important trends in the organization of a full and impartial mechanism forcharging, the development of a uniform methodology for calculating the specific amount of environmental payment. One of the importanttrends in the organization of a full and impartial mechanism for charging, the development of a uniform methodology for calculatingthe specific amount of environmental payment